PENGEMBANGAN E-CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN PEMAHAMAN TEKS NARASI SISWA KELAS IV SDN 1 MACANAN KECAMATAN LOCERET KABUPATEN NGANJUK - Salsabila Nur Fitriana; Kukuh Andri Aka; Endang Sri Mujiwati (Jurnal Manajemen Pendidikan, 2026)
The purpose of this study was to determine the validity, practicality, and effectiveness of local wisdom-based picture e-stories on Narrative Text material in grade IV of SDN 1 Macanan. The research method applied in this study is R&D (Research and Development) using the ADDIE model which includes 5 stages, namely (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The instruments used were expert validity questionnaires, teacher practicality questionnaires, student questionnaires, and questions. The results of the study showed that: (1) Validity was obtained from the assessment of media validators by 90% and material validators by 87.5%, both of which were included in the very valid category. Validation of evaluation questions got a score of 88% with a very valid category; (2) Practicality based on the teacher response questionnaire reached 100%, student responses in the limited trial were 92%, and in the extensive trial were 90%, all of which were in the very practical category; (3) Effectiveness was shown through the results of the limited trial which received an average n-gain score of 0.79 in the high category, and the extensive trial which received an average n-gain score of 0.76 in the high category..